De-Colorization Activity Enhancement of Degussa P25 TiO2 via the Formation of p-n Heterojunction by Carboxylic Modification. Issue 3 (1st January 2015) - Hsiao, Yu-Cheng; Su, Chih-Hao; Hu, Chi-Chang; Rajkumar, Muniyandi
Abstract : The visible-light-driven photocatalytic activity of Degussa P25 TiO2 is effectively promoted by modifiers containing carboxylic groups through impregnating cyclohexanol and a low-temperature heating treatment. The superficial TiO2 modified with the organic modifiers creates certain low band-gap states to enhance its visible-light activity. The carboxylic-modified TiO2 dispersed on the P25 surface shows the p-type semiconductor characteristics, confirmed by the photocurrent responses under the open-circuit state and blue-light irradiation. Accordingly, a p-n heterojunction between the superficial modified TiO2 and underneath P25 enhances the separation of photo-excited electron/hole pairs, resulting in the higher photocatalytic activity. During the photo-electrocatalytic de-colorization test, the photo-excited electrons are further withdrawn by the positive potential bias toward the graphite cathode through the electric circuit, which favors the oxygen reduction reaction (ORR) of two-electron transfer to effectively generates H2 O2 for organic pollutants decomposition. Therefore, methylene blue (MB) can be efficiently de-colorized on the carboxylic-modified P25 under the visible-light irradiation meanwhile the de-colorization rate is enhanced under the photo-electrocatalytic mode.